2014
DOI: 10.1186/preaccept-2101307024135398
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and role in malaria transmission of Anopheles funestus populations from Zambia and Zimbabwe

Abstract: This is the first record of An. funestus mtDNA clade II occurring in Zambia. No evidence was found to suggest that the clades are markers of biologically separate populations. The ability of An. funestus to withstand prolonged exposure to pyrethroids has serious implications for the use of these insecticides, either through LLINs or IRS, in southern Africa in general and resistance management strategies should be urgently implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 7 publications
2
48
0
Order By: Relevance
“…exposed to deltamethrin in Côte d’Ivoire and Uganda, respectively [ 13 , 15 ], and a recent study in Zambia (recording knockdown rather than mortality) found time to knockdown with deltamethrin was approximately 14-fold higher in a wild population of An. funestus than in the laboratory susceptible strain [ 16 ]. The highest resistance ratios reported to date are from Burkina Faso where, in 2012, An.…”
Section: Discussionmentioning
confidence: 99%
“…exposed to deltamethrin in Côte d’Ivoire and Uganda, respectively [ 13 , 15 ], and a recent study in Zambia (recording knockdown rather than mortality) found time to knockdown with deltamethrin was approximately 14-fold higher in a wild population of An. funestus than in the laboratory susceptible strain [ 16 ]. The highest resistance ratios reported to date are from Burkina Faso where, in 2012, An.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae and An. funestus in Zambia to varying degrees, particularly in areas with high IRS coverage [10,11]. Zambia has recently switched to spraying with organophosphates, specifically pirimiphos-methyl (Actellic CS) to combat this resistance.…”
Section: Introductionmentioning
confidence: 99%
“…funestus due to its strong association with humans and human habitations [1,2]. However, the development of insecticide resistance across the region [5,6] has seen vector control programs compromised in some places [7][8][9]. This has also played an important role in the slow-down of the gains made in malaria control over the past 10 years in Africa [10,11].…”
mentioning
confidence: 99%